Pengaruh Pemberian Ekstrak Etanol Daun Pandan Wangi (Pandanus amaryllifolius Roxb) Terhadap Kolesterol Mencit (mus musculus): EFFECT OF ETHANOL EXTRACT OF FRAGRANT PANDAN LEAVES (Pandanus amaryllifolius Roxb) ON CHOLESTEROL MICE (Mus musculus) - Hashary, A. rufaidah (Program Studi Farmasi, Universitas Islam Makassar, 2023)
Pandan Wangi leaves (Pandanus amaryllifolius Roxb) contain flavonoid chemicals found in fragrant pandan leaves which have antimicrobial, anticancer, antidiabetic, and lower cholesterol levels. The purpose of this study was to determine the effect of fragrant pandan leaf extract (Pandanus amaryllifolius Roxb) in lowering cholesterol in mice (Mus musculus) and to determine what dose of fragrant pandan leaf extract could lower cholesterol well in mice. The research method used is an experimental method using a maceration extraction process. This study used 15 mice (Mus musculus), then given fragrant pandan leaf extract (Pandanus amaryllifolius Roxb) with dosage variations of 40 mg/kgBW, 80 mg/kgBW, 160 mg/kgBW, negative control (Na.CMC), and a positive control (Simvastatin) previously induced by Alloxan. Cholesterol level examination was carried out twice, namely after Alloxan was induced and after being treated using a Nesco GCU measuring instrument. The result of this research is that pandan fragrant leaf extract (Pandanus amaryllifolius Roxb) can reduce cholesterol levels in the blood of mice (Mus musculus) where a dose concentration of 80 mg/kgBW shows the best dose in lowering cholesterol levels.